2010
DOI: 10.1007/s10548-010-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Greater Low Frequency EEG Activity in Normal Immaturity and in Children with Epilepsy Arise in the Same Neuronal Network?

Abstract: Greater low frequency power (<8 Hz) in the electroencephalogram (EEG) at rest is normal in the immature developing brain of children when compared to adults. Children with epilepsy also have greater low frequency interictal resting EEG activity. Whether these power elevations reflect brain immaturity due to a developmental lag or the underlying epileptic pathophysiology is unclear. The present study addresses this question by analyzing spectral EEG topographies and sources for normally developing children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Third, our frequency filtering precluded investigation of frequencies in the HFO range and below 6 Hz. A recent study suggested that low‐frequency oscillations may be related to the abnormal development of functional networks [Michels et al, ], which should be investigated in future studies. Fourth, we could not assess the influence of spikes on network and local motor cortex activity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our frequency filtering precluded investigation of frequencies in the HFO range and below 6 Hz. A recent study suggested that low‐frequency oscillations may be related to the abnormal development of functional networks [Michels et al, ], which should be investigated in future studies. Fourth, we could not assess the influence of spikes on network and local motor cortex activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of a phasic event-related increased FM-theta power with load during the maintenance interval replicates previously published EEG/MEG work on WM during a similar task [5] , [6] , [7] , [67] . Since rest activity was subtracted for both load conditions and age groups, task-related group differences (children > adults) cannot simply reflect the well-known increase of low frequency resting state power in children [18] , [19] , [68] . Although FM-theta power has been observed even in young children [69] , [70] , our results demonstrating stronger FM-theta power in school-aged children most likely reflect brain immaturity, as children performed significantly worse than adults.…”
Section: Discussionmentioning
confidence: 99%
“…Such states are low arousal states like sleep (Steriade et al, 1993;Tsai et al, 2010) or anesthesia (John et al, 2001), and neuropathology (Llinas et al, 1999;Michels et al, 2011a;Michels et al, 2011b;Sarnthein et al, 2003). Low arousal states and neuropathologic conditions can be seen as states of lower brain functioning.…”
Section: Maturation Of Eeg-bold Coupling Patternsmentioning
confidence: 99%